The degree of practicing the educational supervision skills by school principle as a resident supervisor from the teachers' perspective at Qasbat Almafraq directorate of education in Jordan - Harahsha, Emad Kalaf (Journal of Educational and Psychological Sciences, 2020)
The study aimed at identifying the degree that the school principal as a resident supervisor practices the skills of educational supervision from the teachers’ perspective in the light of gender, qualification, and years of experience variables. The researcher used the descriptive approach, and developed a questionnaire consisting of (31 items). The questionnaire was divided into four fields. The randomly chosen sample of this study consisted of (365) male and female teachers from Qasbat Almafraq directorate of education. The results of the study showed that the degree of practicing educational supervision skills by the school principal as a resident supervisor from the teachers’ perspective was intermediate scoring (3.47). According to the fields, the highest average was for the professional growth field by scoring (3.76), then comes the human skills field scoring intermediate average (3.63), then the teaching planning field scoring (3.27), finally the curriculum development field scoring (3.26). The study found that there are statistically significant differences for the study sample estimates on the degree of practicing educational supervision skills by the school principal as a resident supervisor from the teachers’ perspective due to the variables of sex and qualification. For sex variable, the results came in favor of females. For the qualification variable, the results were in favor of those who have postgraduate studies. It found that there are not any statistically significant differences due to the variable of years of experience. Based on the results of the study, the researcher recommends developing supervisory skills among school principals through their participation in training courses to enhance these skills.
Keywords: The degree of practicing; supervision skills; schools principals; Qasbat Almafraq directorate of education; jordan; practicing